Horner Syndrome Secondary to Thyroid Surgery. (4th January 2017) - Demiral, Meliha; Binay, Ciğdem; Simsek, Enver; Ilhan, Hüseyin
Abstract : Horner syndrome (HS), caused by an interruption in the oculosympathetic pathway, is characterised by myosis, ipsilateral blepharoptosis, enophthalmos, facial anhydrosis, and vascular dilation of the lateral part of the face. HS is a rare complication of thyroidectomy. A 15-year-old female patient presented with solitary solid and large nodule in the right thyroid lobe. Ultrasound-guided fine-needle aspiration was performed and the cytological examination results were undefined. The patient underwent a total thyroidectomy. On postoperative day 2, she developed right-sided myosis and upper eyelid ptosis. HS was diagnosed. Interestingly, the patient exhibited an incomplete clinical syndrome with the absence of vasomotor symptoms. We herein report a case of HS in a 15-year-old female patient after total thyroidectomy. The possible causes of HS were ischaemia-induced nerve damage and stretching of the cervical sympathetic chain by the retractor during thyroidectomy. Clinicians should be aware of the possibility of this rare but important surgical complication.